Pengaruh Penjernihan Minyak Jelantah Menggunakan Nasi Terhadap Sifat Fisikokimia Minyak - Sidiq, Aqil Marsya; Putra, Ananda; Amelia, Fitri; Pernadi, Niza Lian; Rizki, Suci Yulia; Nizar, Umar Kalmar (Periodic, 2024)
The increased demand for cooking oil has led to a corresponding rise in its consumption. To address this situation, individuals often resort to reusing cooking oil, despite its unsuitability for consumption. The repeated use of cooking oil at high temperatures induces the hydrolysis of triglycerides into free fatty acids. Consequently, this research aims to refine the quality of used cooking oil through its purification using rice, rendering it suitable for reuse. Rice is rich in amylose and amylopectin, both of which feature -OH groups that can interact with -COOH groups present in free fatty acids within used cooking oil. In the process of used cooking oil purification, rice serves as an adsorbent. The findings of this study exhibit an improvement with an increase in the amount of rice used in the purification of cooking oil. Furthermore, the utilization of rice as an adsorbent during the cooking oil purification process leads to a reduction in density to 0.9454 g/mL, a decline in the acid number to 2.0797 mg KOH/g, an augmentation of flow rate to 0.3141 mL/s, and an elevation of the hoarding number to 77.1842 mg KOH/g within the used cooking oil.